2004
DOI: 10.1103/physrevb.69.205322
|View full text |Cite
|
Sign up to set email alerts
|

Fractional quantum Hall states of clustered composite fermions

Abstract: The energy spectra and wavefunctions of up to 14 interacting quasielectrons (QE's) in the Laughlin ν = 1 3 fractional quantum Hall (FQH) state are investigated using exact numerical diagonalization. It is shown that at sufficiently high density the QE's form pairs or larger clusters. This behavior, opposite to Laughlin correlations, invalidates the (sometimes invoked) reapplication of the composite fermion picture to the individual QE's. The series of finite-size incompressible ground states are identified at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
122
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 57 publications
(134 reference statements)
8
122
0
Order By: Relevance
“…The experimental evidence for such higher order states bring into question the validity of the weakly interacting CF framework [4]. While these higher order fractions were actually predicted in the earlier hierarchical model [5,6], it was argued that the CF model may account for these new fractions when CF residual interactions are incorporated beyond the mean-field level [7,8,9,10,11,12,13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental evidence for such higher order states bring into question the validity of the weakly interacting CF framework [4]. While these higher order fractions were actually predicted in the earlier hierarchical model [5,6], it was argued that the CF model may account for these new fractions when CF residual interactions are incorporated beyond the mean-field level [7,8,9,10,11,12,13,14].…”
mentioning
confidence: 99%
“…This ordering assumes full spin polarization in the full range 1/3 < ν < 2/5. While this assumption has been debated [7,8,13,14], transport experiments with tilted magnetic fields indicate that at least the state at ν = 4/11 is fully spin polarized for B T > 10 T . In the following we show that the filling factor dependence of the SF peak energy clarifies this issue.…”
mentioning
confidence: 99%
“…In fact, almost all the existing finite-size numerical calculations [13][14][15][16][17][18] seem to favor a partially spin polarized ground state for the experimentally observed 4/11 state. However, the numerical simulations were carried out in 2DES of zero thickness.…”
mentioning
confidence: 99%
“…Yet, its origin remains elusive. Several proposals [13][14][15][16][17][18] have been made. Among them, the numerical simulations by Wójs, Yi, and Quinn (WYQ) [15] showed that a spin-polarized 4/11 FQHE state is an unconventional FQHE state of CFs and, possibly, a new nonAbelian state.…”
mentioning
confidence: 99%
See 1 more Smart Citation